[Retracted] Clinical characteristics and treatment outcomes of skin and soft tissue infections in children: a prospective study - Nguyen, Huu Chau Duc; Cao, Thi Nhung; Nguyen, Van Tuy (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
The article is retracted on the author request